Cognitive disorders and their dynamics in patients with schizophrenia - Gailienė, D. (Psichologija, 1982)
The article describes the evaluation of cognitive disorders, such as attention concentration and attentional shift, visual-motor coordination, memory span, certain constructional abilities in patients with schizophrenia. The repeated study was carried out after 3.5 years showed that in spite of illness dynamics, cognitive disorders remain unchanged, but patients’ social orientation decreases.
Keywords: schizophrenia; cognitive processes; schizophrenia diagnostics